Comparing the effects of microwave radiation on 6-gingerol and 6-shogaol from ginger rhizomes (Zingiber officinale Rosc). - Hui Teng; Kemueli T Seuseu; Won-Young Lee; Lei Chen (PLoS ONE, 2019)
The active component obtained from ginger is a high value-added product, but continued research is required for improved extraction techniques that will lead to better quality extracts and greater yields. In this study, major functional compounds of 6-gingerol and 6-shogaol in ginger rhizomes (Zingiber officinale Rosc) were extracted using microwave assisted extraction (MAE). Possible ranges for optimal MAE conditions were predicted by merging of the contour plots of each response to observe the overlapping area of all responses. Optimal conditions predicted were ethanol concentration of 70%, extraction time of 10 min, and microwave power of 180 W. Verification tests carried out at a set of random condition within the above mentioned optimal ranges, which got experimental values for total soluble solid yield, antioxidant activity, 6-gingerol and 6-shogaol of 30.0±0.8%, 87.8±0.8%, 2.8±0.6 mg/g and 1.3±0.5 mg/g, respectively. Analysis results showed that steamed ginger sample contained lower 6-gingerol content, soluble solid as well as reduced antioxidant activity, but higher in 6-shogaol as compared with fresh sample.